0509 Patient and Provider Perspectives on Patient-Centered Outcomes in Sleep Apnea. (27th April 2018) - Havens, C; Seixas, A; Jean-Louis, G; Buysse, D; Kushida, C; Mullington, J; Redline, S; Mehra, R; Stone, K; Amdur, A; Stepnowsky, C; Gooneratne, N; et al.
Abstract: Introduction: Engaging patients and stakeholders in research is key to identifying patient-centered outcomes (PCOs). Our goal was to engage patients, providers, and other stakeholders across the entire spectrum of sleep medicine to identify PCOs related to obstructive sleep apnea (OSA). A secondary aim was to examine the patient-centeredness of research priorities in OSA by comparing patient's ratings of priorities to those of providers. Methods: Two conferences were held, which engaged eight stakeholder groups to ascertain important PCOs for OSA. Fifteen PCO domains were identified through semi-structured interviews of patients with OSA. An anonymous internet-based survey was administered to patients with OSA, providers, and other stakeholders through social media, to measure prioritization of outcomes on 100 mm visual analogue scales, ranging from 0 (unimportant) to100 (highly important) for each of the 15 PCO domains. Results: The 1088 total respondents included 916 patients with OSA (29% male; age 56.7 ± 11.7 years) and 56 providers. The following six PCO domains had the highest patient ratings: Prevent long-term complications of sleep disorders (89 ± 19 [SD] on visual analogue scale); improve daytime functioning (88 ± 22); reduce mortality (89 ± 22); improve general health (81 ± 26); promote treatment adherence (80 ± 26); and improve sleep symptoms (86 ± 22; GLM; F=2.3; P=0.003). Other PCOs were improve sleep hygiene; reduce complications of co-existing medical conditions; prevent hospitalizations; improve access to healthcare; improve patient education; better manage treatment complications; treat coexistent mental health issues; better access to provider; and early detection of sleep disorder. After adjusting for covariates (age, sex, and race), there were no significant differences between patient and provider ratings of the 15 PCO domains (GLM; F=0.03; P=0.86). Age (F=13.8; P<0.0001) and sex (F=8.6; P=0.004) of the respondents played an important role in prioritizing PCOs. Conclusion: These engagement efforts between patients and providers have yielded important insights about PCOs in sleep medicine. Good agreement was observed between patients and providers with regards to PCOs in OSA. The highly ranked PCO domains provide targets for future patient-centered clinical-trials. Support (If Any): PCORI-EAIN-3394-UOA.